Glycerin in feeding of lambs finished in feedlot: Quantitative characteristics of carcass and qualitative characteristics of meat - D'Aurea, E. M.O. [UNESP]; Ezequiel, J. M.B. [UNESP]; Santos, V. C. [UNESP]; D'Aurea, A. P. [UNESP]; Carvalho, V. B. [UNESP]; Almeida, M. T.C. [UNESP]; Perez, H. L. [UNESP] (FapUNIFESP (SciELO), 2018)
This study was conducted to evaluate absence and the inclusion of glycerin in the diet of feedlot finished lambs on carcass characteristics and meat quality in the semimembranosus muscle. Forty males of the breed 1/2 Dorper 1/2 Santa Inês weaned with average age of 90 days and average weight of 21±2.3kg were included. The treatments consisted of two diets: G0 - absence of glycerin and G10 - inclusion of 10% glycerol. The experimental design was completely randomized, with two treatments and 20 repetitions. There was effect to slaughter weight (P=0.041) and cold carcass yield (P=0.019) between treatments. We conclude that the lambs fed the inclusion of glycerin (10%) showed better cold carcass yield and lower slaughter weight without changing the other characteristics studied.

O presente trabalho foi conduzido com o objetivo de avaliar a ausência e a inclusão de glicerina na dieta de cordeiros terminados em confinamento, sobre as características da carcaça e a qualidade da carne no músculo semimembranosus. Foram utilizados 40 cordeiros machos, não castrados, da raça 1/2 Dorper 1/2 Santa Inês, desmamados com idade média de 90 dias e peso médio inicial de 21±2,3kg. Os tratamentos constituíram-se de duas dietas: G0 - ausência de glicerina e G10 - inclusão de 10% de glicerina na MS. O delineamento experimental utilizado foi o inteiramente ao acaso, com dois tratamentos e 20 repetições. Observou-se efeito para peso de abate (P=0,041) e rendimento de carcaça fria (P=0,019) entre os tratamentos. Conclui-se que os cordeiros alimentados com a inclusão de glicerina (inclusão de 10% de glicerina na MS) apresentaram melhor rendimento de carcaça fria e menor peso de abate, sem que fossem alteradas as demais características estudadas.
Glicerina na alimentação de cordeiros terminados em confinamento: Características quantitativas da carcaça e qualitativas da carne950-1958
Keywords: Carcass; Carcaça; Cordeiro; Glicerina; Glycerin; Lamb; Meat quality; Qualidade da carne